Analysis of the application and impact of carbon dioxide media on the corrosion state of oil and gas facilities - Rafael R. Kantyukov; Dmitry N. Zapevalov; Ruslan K. Vagapov (Записки Горного института, 2021)
Products of several currently operated production facilities (Bovanenkovskoye, Urengoyskoye oil and gas condensate fields, etc.) contain an increased amount of corrosive CO2. Effect of CO2 on the corrosion of steel infrastructure facilities is determined by the conditions of its use. Carbon dioxide has a potentially wide range of applications at oil and gas facilities for solving technological problems (during production, transportation, storage, etc.). Each of the aggregate states of CO2 (gas, liquid and supercritical) is used and affects the corrosion state of oil and gas facilities. Article analyzes the results of simulation tests and evaluates the corrosion effect of CO2 on typical steels (carbon, low-alloy and alloyed) used at field facilities. The main factors influencing the intensity of carbonic acid corrosion processes in the main conditions of hydrocarbon production with CO2, storage and its use for various technological purposes are revealed. Development of carbon dioxide corrosion is accompanied and characterized by the localization of corrosion and the formation of defects (pitting, pits, etc.). Even alloyed steels are not always resistant in the presence of moisture and increased partial pressures of CO2, especially in the presence of additional factors of corrosive influence (temperature, aggressive impurities in gas, etc.).